ANALYSIS OF THE APPLICATIONS OF SME ACCOUNTING APPLICATIONS IN RECORDING THE FINANCIAL STATEMENTS OF FIRDAUS CUCIAN BOGOR - Maryani, Leni; Yogaswara, S. Marten; Natawijaya, Thania Marsella Chandra; Sopiansah, Veri Aryanto (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This research aims to determine the application, limitations faced and the efforts made by Firdaus Cucian Bogor in using the UKM Accounting application. The research method used is qualitative descriptive. The research results show that the application of the SME Accounting application was well received because it helps and makes it easier to produce financial reports. Limitations in its application are the cashier's lack of skill in the fields of finance and information technology, the cashier still lacks discipline in inputting transactions, and the cashier's cell phone does not yet have the facilities to access the application. The limitation of the application is that there is no facility to produce notes on financial reports according to SAK EMKM. Efforts to overcome limitations include providing basic financial management or accounting training, requiring cashiers to input transactions into the application, providing smartphone facilities and making notes on financial reports manually.